ANALISIS KEPUASAN KONSUMEN TERHADAP PEMBELIAN ULANG (REPURCHASE INTENTION) DALAM PEMBELIAN EMAS UNTUK INVESTASI DI MASA PANDEMI - Diandra Ariani Syafitri (2022)
This study analyzes consumer satisfaction with repurchasing gold for investment during the pandemic. The purpose of the study was to analyze consumer satisfaction, products, services, and prices for repurchasing in the purchase of gold for investment during the pandemic. This research is quantitative in nature by distributing questionnaires to 110 buyers of gold buying and selling who have purchased gold more than once during the pandemic. This research uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) alternative with Smart-PLS 3.3.3 program. The results of data analysis show that: (1) Consumer Satisfaction has a significant effect on Repurchase Intention (2) Meanwhile, Product, Service, and Price have no significant effect on Repurchase Intention.